The Role of Adipokines in Spinal Disease: A Narrative Review - Jake M. McDonnell; Stacey Darwish; Joseph S. Butler; Conor T. Buckley (JOR Spine, 2025)
ABSTRACT Background Adipokines are bioactive molecules secreted by adipose tissue that influence both local and systemic physiological processes. Although adipokine dysregulation has been widely implicated in the pathogenesis of cardiovascular, gastrointestinal, nervous, immune, and musculoskeletal disorders‐ especially osteoarthritis, rheumatoid arthritis, and osteoporosis‐ their involvement in spinal pathology remains comparatively underinvestigated. Recent evidence indicates that certain adipokines may influence spinal disease progression by affecting bone, intervertebral discs, musculature, and neural structures. Methods A comprehensive literature review was conducted to evaluate preclinical and clinical studies investigating the role of adipokines in spinal pathology. PubMed and related databases were searched for studies reporting associations between adipokine expression and structural or functional changes in spinal tissues, including vertebral bone, intervertebral discs, paraspinal muscles, spinal ligaments, and the spinal cord. Particular attention was given to mechanistic insights and translational relevance. Results The review identified emerging evidence implicating several adipokines, including leptin, adiponectin, resistin, and visfatin, in degenerative and inflammatory changes across various spinal structures. Adipokines were found to influence matrix degradation, bone turnover, muscle atrophy, and neural inflammation through cytokine signaling, oxidative stress, and metabolic dysregulation. However, findings are often heterogeneous and context‐dependent, with limited longitudinal or interventional data. Conclusions Adipokines represent a promising yet underexplored avenue in spinal disease research. Their diverse functions in both structural and metabolic regulation highlight their potential as both biomarkers and therapeutic targets. Further mechanistic and clinical studies are needed to elucidate causal relationships and therapeutic efficacy, particularly in degenerative spine disorders.